COMPREHENSIVE ANALYSIS OF THE CONCEPTS OF STRESS AND ANXIETY FROM THE PERSPECTIVE OF PSYCHOLOGY - Hashimi, Sayed Abas; Dadman, Enayatullah (CV. Radja Publika, 2024)
This paper provides a comprehensive examination of the concepts of stress and anxiety within the realm of psychology. Drawing from theoretical frameworks, empirical research, and clinical observations, it aims to elucidate the similarities and distinctions between these two constructs. By integrating multidimensional perspectives encompassing psychological, neurobiological, and clinical dimensions, this paper contributes to a deeper understanding of the underlying mechanisms driving stress and anxiety-related phenomena. Furthermore, it explores implications for assessment, intervention, and treatment strategies, thereby addressing the complex interplay between psychological distress and mental well-being.